METHODOLOGICAL EDUCATION CHARACTER OF COORDINATING MOVEMENTS IN 14 AND 15 YEAR OLD BOXERS - Saulea George-Dan (Editura Univeristatii "Stefan cel Mare" din Suceava, 2021)
This article describes in detail the methodological education character of coordinating movements in boxers aged 14-15, this age being considered the most favorable and suitable for the education, development and training of all coordination skills. All possible components of these capabilities are outlined and the most relevant aspects are highlighted, for their inclusion in the training process with future boxing performers. Being presented in their algorithmic form, with concrete explanations on the content and essence of practical application of the coordinating components, this information can serve as a very useful teaching material for coaches and athletes in the multiannual process of training future champions in this difficult sport event.